Management of Vitamin D Deficiency Among the Under-Five Children Residing in Coastal Areas of Karnataka: A Study Protocol - Mamatha Shivananda Pai; Reshma R Kotian; Suneel C Mundkur; Shobha U Kamath; Anjeline D'Souza; Bhavana B Bhat; Sangeetha M Acharya (National Journal of Community Medicine)
Introduction: Vitamin D deficiency has become the new normalcy due to rapid transition of lifestyles among the people globally. Vitamin D is synthesized in the body due to exposure of skin to sunlight. Correction of vitamin D deficiency poses a major demand due to its action on bone and muscle health. The objective of this study is to assess the effectiveness of sun exposure and Vitamin D supplement and Vitamin D supplements alone on serum vitamin D levels among the under-fives.